Soil Preparation and Liming for Vegetable Gardens - James M. Stephens; Guodong Liu (EDIS, 2013)
Probably the most physical part of vegetable gardening is preparing the soil for planting. In large gardens, mechanical equipment, such as rototillers or tractor-drawn plows, often is necessary, and it may be practical to rent such equipment or hire someone. However, in smaller gardens, the task can be accomplished with a spade, spading fork, or shovel. Much depends on the type of roots and vegetation that must be removed. This 2-page fact sheet was written by James M. Stephens and Guodong Liu, and published by the UF Department of Horticultural Sciences, June 2013.